Pemanfaatan Internet Of Things Pada Lampu - Muhtajuddin Danny; Wahyudi Wahyudi (Jurnal SIGMA, 2019)
Limited power supply is required to conserve its use. One of the things that can be done to save electricity is to use the house lights as needed. Open source operating systems on android phones can be used to make the house light controller applications using the Arduino UNO (Microcontroller ATmega328) and relay instead of a switch. Android application is used as input commands to the circuit arduino UNO (microcontroller ATmega328) through media liaison Bluetooth module. Arduino UNO will respond to input with the output of a logic low (0V) and logic high (5V) via pins that have been determined, the pins are connected to the Relay module. Relay module is used instead of a switch that is connected to the lamp house. When it gets input logic low (0V) the relay will be active and will supply power to the light so that the light is on, and when it gets a high logic input (5V) relay will not be activated so that the flow of electricity to the lights and the lights will cut off the dead.